Dampak Overcrowding terhadap Narapidana Rumah Tahanan Negara Kelas IIB Ruteng - Frederich Ramiga Seputra Gaut; Karolus K. Medan; Heryanto Amalo (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
Prison, is an institution whose existence is inseparable from law enforcement in Indonesia. Unlike prisons, Rutan functions as a temporary detention place for suspects or defendants who are undergoing the trial process. Currently, almost all prisons and prisons in Indonesia are experiencing an overcrowding crisis with an overcrowding rate. 92%. This condition is like a time bomb ready to explode. Extreme overcrowding in prisons and prisons has various negative impacts. Overcrowding in correctional facilities and prisons is a serious problem that must be overcome immediately. The impact is not only on the health and safety of residents, but also on the effectiveness of coaching and the state budget. This study aims to find out and discuss the impact of overcrowding on class IIB state prison inmates in Ruteng Regency. This research is an empirical legal research or empirical juridical research supported by a statuecause approach using primary data and secondary data collected using observation, documentation and interview techniques conducted with 33 informants. The data obtained was processed using editing techniques, data classification, data verification and description after which it was analyzed in a qualitative descriptive manner. The results of the study showed that (1) Overcrowding in Ruteng Class IIB Prison was caused by several interrelated factors. First, the limited capacity of Ruteng Detention Center. Second, the crime rate has increased in three districts. Third, the penal policy is not yet effective. Fourth, the low legal awareness of the public also plays a role in the increase in crime rates. (2) Overcrowding in Ruteng Class IIB Prison has a significant impact on inmates, especially in fulfilling their rights including the right to inmate health, the right to security, and the right to rehabilitation. Social coaching and reintegration programs cannot run effectively due to limited resources and space.